Toughness and microstructure of 13Cr4NiMo high-strength steel welds - Bilmes, Pablo David (2000)
The microstructures and tensile, Charpy, and crack tip opening displacement (CTOD) properties of 13Cr4NiMo soft martensitic stainless steel flux cored are welding process (FCAW) weld metals have been studied through different applied postweld heat treatments (PWHT). Phases and microstructural characteristics have been analyzed by scanning electron microscopy (SEM) and x-ray diffraction. The effect of the tempering and double tempering, with and without previous solution annealing, on the impact and fracture toughness has been studied. The role of the retained austenite resulting from tempering has been recognized, and it is suggested that the austenite particles improve the toughness of the welds through their transformation by the transformation-induced plasticity (TRIP) mechanism.